The influence of using volcanic ash and lime ash as filler on compressive strength in self compacting concrete. (March 2018) - Karolina, Rahmi; Panatap Simanjuntak, Murydrischy
Abstract: Self Compacting Concrete (SCC) is a technology which is developing today in which concrete solidifies by itself without using vibrator. Casting conventional concrete which has a lot of reinforcement bars sometimes finds difficulty in achieving optimal solidity. The method used to solve this problem is by using SCC technology. SCC was made by using filler, volcanic ash, and lime ash as the filling materials so that the concrete became more solid and hollow space could be filled up. The variation of using these two materials was 10%, 15%, 20%, and 25% of the cementitious mass and using 1% of superplasticizer from cementitious material. The supporting testing was done by using the test when the concrete was still fluid and when it was solid. Malleable concrete was tested by using EFNARC 2002 standard in slump flow test, v-funnel test, l-shaped box test, and j-ring test to obtain filling ability and passing ability. In this malleable lime concrete test, there was the decrease, compared with normal SCC concrete without adding volcanic ash and lime ash. Testing was also done in solid concrete in compressive strength, tensile strength, and concrete absorption. The result of the testing showed that the optimum tensile strength in Variation 1, without volcanic ash and lime ash – with 1% of superplasticizer was 39.556 MPa, the optimum tensile strength in Variation 1, without volcanic ash and lime ash- with 1% of super-plasticizer was 3.563 MPa, while the value of optimum absorption which occurred in Variation 5 (25% of volcanic ash + 25% of lime ash + 50% of cement + 1% of superplasticizer) was 1.313%. This was caused by the addition of volcanic ash and lime ash which had high water absorption.